1999
DOI: 10.1111/1468-0009.00150
|View full text |Cite
|
Sign up to set email alerts
|

Infected Physicians and Invasive Procedures: National Policy and Legal Reality

Abstract: Recent reports of the transmission of hepatitis B, hepatitis C, and HIV from physicians to patients during invasive procedures have again raised the question of whether physicians infected with bloodborne pathogens should perform invasive procedures that place patients at risk, and if so, under what conditions. Attempts to formulate a national policy on this subject must consider the competing interests of the patient's welfare versus the physician's livelihood. A review of the legal aspects of this topic is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
6

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
(24 reference statements)
0
17
0
6
Order By: Relevance
“…The current German [Robert Koch-Institut, 1999;Gerlich et al, 2001] and Canadian regulations [Health Canada, 1998], for instance, adopt this more conservative position. To ®nally resolve the controversial issue [Tereskerz et al, 1999;Cockcroft, 2000;Heptonstall, 2000;AlvaradoRamy et al, 2001], we believe, a series of further carefully conducted look-back studies is needed that should involve a broad spectrum of exposure-prone, high-risk procedures from all medical specialties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current German [Robert Koch-Institut, 1999;Gerlich et al, 2001] and Canadian regulations [Health Canada, 1998], for instance, adopt this more conservative position. To ®nally resolve the controversial issue [Tereskerz et al, 1999;Cockcroft, 2000;Heptonstall, 2000;AlvaradoRamy et al, 2001], we believe, a series of further carefully conducted look-back studies is needed that should involve a broad spectrum of exposure-prone, high-risk procedures from all medical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the mostly asymptomatic course of HCV infection [Shimotohno and Feinstone, 1997], one cannot exclude, however, that HCV physician-to-patient transmission occurred more often, but remained undetected. Consequently, a controversial discussion has emerged in the medical community concerning the real number and potential public health implications of such nosocomial infections as well as possible restrictions in the practice of HCV-infected health-care workers performing exposure-prone procedures [CDC, 1991;Tereskerz et al, 1999;Cockcroft, 2000;Heptonstall, 2000;AlvaradoRamy et al, 2001]. To achieve acceptable estimates of the existing threat that may form a reliable basis for future recommendations on the guidance and management of HCV-positive medical staff members, a series of carefully conducted retrospective studies of individuals treated by HCV-infected personnel is needed [Ross et al, 2000b].…”
Section: Introductionmentioning
confidence: 99%
“…and colleagues undertook a legal and policy analysis of this issue, which concluded that both legal and medical realities call for a straightforward policy that provides clear guidance. The current project is a continuation of this previous work [46]. Recognizing that an essential component of future policy development is a balanced approach that fosters representation and protection of all of the parties involved, a multidisciplinary national committee was established.…”
Section: Methodsmentioning
confidence: 99%
“…Die Wahrscheinlichkeit einer HCV-Serokonversion nach Nadelstichverletzungen beträgt etwa 2,2% [14,33,38,39]. HCV-Infektionen, die ein Versicherter im Gesundheitsdienst, in der Wohlfahrtspflege, in einem Laboratorium oder bei einer ähnlich infektionsgefährdenden Tätigkeit erleidet, fallen also prinzipiell unter die Berufskrankheiten ( § 1 in Verbindung mit Anlage 1, Nr.…”
unclassified
“…Daher versucht man derzeit in Deutschland, die weitere Beschäftigung HCV-positiven medizinischen Personals mittels eines Verfahrens zu regeln, das sich an britische und nordamerikanische Richtlinien anlehnt. Der Schwerpunkt zielt nicht auf die Verhängung von Berufsverboten, sondern auf die Beratung des Beschäf-tigten durch ein lokales Expertengremium, dem Ärzte unterschiedlicher Fachgebiete als Gutachter angehören kön-nen [12,31,38,39]. Das Gremium entscheidet über die Fortführung der bisherigen Tätigkeit sowie Art und Umfang eventueller Einschränkungen.…”
unclassified